Pengaruh Kepercayaan, Kemudahan, dan Manfaat terhadap Keputusan Pembelian Menggunakan Metode Pinjaman Online Spaylater pada Mahasiswa di Kabupaten Bangkalan - Zahroh, Aminatus; Septiana, Aldila; Arief, R. Zaiful (Jurnal Pendidikan Ekonomi Undiksha, 2023)
In the current era of digitalization, everything can be obtained easily. As digital transactions develop, it becomes easier for customers to get the goods they want without having to leave their homes, but behind the convenience offered there are still many factors that make consumers hesitate to shop online including the risk of fraud in terms of both quality and payment systems. In a way, now the PayLater feature has become an alternative payment option that is very popular and favored by the public with its convenience. But behind the convenience and practicality offered, not a few people and even students are victims of online loan fraud. This research is included in the quantitative research with purposive sampling method. The number of samples used was 100 students, the data was obtained by distributing questionnaires. Based on the research results, it is known that trust and benefits influence purchasing decisions, and convenience does not affect purchasing decisions using the Shopee Paylater method. This shows that trust and benefits in an item or service greatly affect students in carrying out daily online transaction activities, if consumers already feel that there is a benefit for them then they are happy to use Spaylater services.